Design of a Website-Based Medical Record Information System with QR Code for Fast Data Access: A Case at Dr. Radi Yarman’s General Practice - Aghnia Putri; Utami Mizani Putri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Medical record data management at Dr. Radi Yarman's General Practice is currently still conducted manually using registration books and physical archives. This leads to several constraints, such as slow retrieval of patient medical history, risks of data loss or damage, and a lack of efficiency in patient services. This study aims to design and develop a website-based medical record information system integrated with QR Code technology to accelerate patient data access. The system development method used is the Waterfall model, which includes requirements analysis, system design, implementation, testing, and maintenance. The system design is modeled using Unified Modeling Language (UML) and Entity Relationship Diagram (ERD), while the implementation uses PHP programming language and MySQL database. The results show that the developed system is capable of digitalizing the medical recording process, storing data centrally, and accelerating patient identification through QR Code scanning. System testing was conducted using the Black Box Testing method to ensure functional features run as planned, as well as Usability Testing to assess ease of use. With this system, the doctor can manage patient visit history, diagnoses, and prescriptions more quickly, accurately, and securely, thereby improving the quality of health services at Dr. Radi Yarman's General Practice.